Visible-Light-Induced Aerobic Oxidation of Tertiary Silanes to Silanols using Molecular Oxygen as an Oxidant - He, Pei; Zhang, Fengmei; Si, Xiaoxi; Jiang, Wei; Shen, Qinpeng; Li, Zhenjie; Zhu, Zhiyang; Tang, Shiyun; Gui, Qing-Wen (Synthesis, 2022)
The photocatalyzed synthesis of silanols from tertiary silanes has been carried out using eosin Y under air. This is a metal-free method that uses a low catalyst loading, atmospheric oxygen as the oxidant, and visible-light conditions (blue light).
Keywords: silanols; oxygen; visible light; eosin Y; photocatalytic oxidation